The influence of socio‐economic background and gender on school attainment in the United Kingdom: A systematic review. Issue 1 (21st June 2019) - Early, Erin; Miller, Sarah; Dunne, Laura; Thurston, Allen; Filiz, Mehmet
Abstract : This narrative systematic review examined relationships between school attainment, socio‐economic status and gender in the United Kingdom from 2000 to 2012. The influence of socio‐economic status was considered at the individual and school level, while gender was examined at the individual level. To ensure consistency among included studies, the Programme for International Student Assessment (PISA) was selected as the attainment measure. Following screening and the application of inclusion/exclusion criteria, 23 studies were included in this review. The most common measures of socio‐economic status were parental occupation, parental education and individual/school mean of economic, social and cultural status. This review found that individual and school level factors of socio‐economic status were consistent in the magnitude and direction of their influence over time. Gender was also a statistically significant indicator of attainment. However, variation was evident in the effects of gender according to the PISA cycle, UK country and subject. This review also provided a critical discussion on the quality of included studies, questioning study reliability owing to variation in reporting sample sizes, data manipulation and summary statistics. The review concluded greater consistency in reporting PISA results, especially descriptive and summary statistics would improve comparability of studies within and between PISA cycles, transparency of methodological approaches and the overall reliability of studies.